PERMASALAHAN PENYESUAIAN DIRI DAN STRATEGI COPING (KASUS TIGA REMAJA BERMASALAH DI BALAI REHABILITASI SOSIAL) - WIDIASTUTI, AJENG AYU; Nuryoto, Sartini ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Self adjustment is an interaction between an individual with himself, the individual with others, as well as individuals with his world in which all the three parties have a reciprocal relationship. When individuals can not adjust to himself, others and the world, a problem would occur. This problem might be faced by the teenagers either as the individuals in society. Therefore, a coping strategy is required in this case to overcome the problem in self adjustment. Due to the underlined issue, this study was aimed to identify the problems of self adjustment and the type of coping strategies developed by the adolescent. The subject of this study was three teenagers of different family background at Social Rehabilitation Centre in Salatiga. The approach of this study was phenomenological qualitative. Results showed that the teenagers faced a variety of adjustment problems and had different coping strategies. Two factors were indicated to influence teenagersâ self adjustment, namely internal and external factors. The internal factor could be classified into three terms